Employee performance of Sharia Bank in Indonesia : The mediation of organizational innovation and knowledge sharing - Zulkifli Zulkifli; Astri Ayu Purwati; Nicholas Renaldo; Zulfadli Hamzah; Muhammad Luthfi Hamzah (Cogent Business & Management, 2023)
Islamic bank is a financial institution that applies the concept of sharia management in its operational activities including human resource management. This study aimed to analyze the influence of competency and Islamic organizational culture in improving employee performance with the mediation of organizational innovation and knowledge sharing. The population of this study were 941 employees of Islamic banks in Pekanbaru, Indonesia and a total of 273 employees were obtained as samples. The data analysis technique used is the Structural Equation Model (SEM) Analysis with AMOS. The study results showed that competency and Islamic organizational culture have a significant positive effect on organizational innovation, Organizational Innovation has a significant positive effect on knowledge sharing, and competency, Islamic organizational culture and organizational innovation have a significant effect on employee performance. Meanwhile, Competency and Islamic Organizational Culture do not have a significant effect on knowledge sharing and knowledge sharing does not have a significant effect on employee performance. The indirect effect test results show that organizational innovation has a mediating role in the influence of competency and Islamic organizational culture on employee performance. Meanwhile, knowledge sharing cannot mediate the influence of competency, Islamic organizational culture and organizational innovation on employee performance.
Keywords: 650; competency; employee performance; Islamic organizational culture; knowledge sharing; organizational innovation